Red cabbage anthocyanins content as a natural colorant for obtaining different color on wool fibers. Issue 3 (27th January 2020) - Barani, Hossein; Maleki, Homa
Abstract : Purpose: Finding blue colorants from natural sources is extremely difficult and, usually, the anthocyanin compounds are used for producing the blue color. This study aims to apply the Red Cabbage as a natural colorant to obtain different colors on wool yarn, as well as specify the optimum dyeing condition by response surface methodology for obtaining a blue color. Design/methodology/approach: The effect of dyeing process parameters such as mordant concentration, dyeing time, pH of dyeing bath and dyeing temperature examined in the color characteristics of the dyed wool samples. Findings: The obtained results indicated that the diverse colors achieve by varying the dyeing process parameters, which is in the range of 26° up to 271°. The non-mordanted dyed wool samples showed a red and red brownish color (Hue angle = 26° up to 70°), and the mordanted dyed wool samples showed a blue and blue-greenish color (Hue angle = 230° up to 271°). The obtained blue color with the optimized dyeing condition presented a considerable good wash and lightfastness. Originality/value: This study provides a promising application of Red Cabbage as a natural colorant for obtaining different colors by varying the dyeing process parameters such as pH and stannous ion concentrations. The stannous ions yielded a co-pigmentation and presented a blue color on wool fibers, which is extremely difficult to obtain with natural colorant.